2013
DOI: 10.1016/j.yjmcc.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, distribution, mobility and oligomeric state of M2 muscarinic acetylcholine receptors in live cardiac muscle

Abstract: M2 muscarinic acetylcholine receptors modulate cardiac rhythm via regulation of the inward potassium current. To increase our understanding of M2 receptor physiology we used Total Internal Reflection Fluorescence Microscopy to visualize individual receptors at the plasma membrane of transformed CHOM2 cells, a cardiac cell line (HL-1), primary cardiomyocytes and tissue slices from pre- and post-natal mice. Receptor expression levels between individual cells in dissociated cardiomyocytes and heart slices were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 34 publications
6
60
0
Order By: Relevance
“…One is that dimeric interactions may be able to occur in a number of distinct ways, including via each of the TMD V-TMD V, TMD VI-TMD VII, TMD IV-TMD V, and TMD I-TMD II interactions (McMillin et al, 2011). Observations that dimer/oligomer interactions of muscarinic receptor subtypes may be transient (Hern et al, 2010;Nenasheva et al, 2013) are certainly consistent with this concept if it predominantly reflects a "kiss and run" phenomenon (Milligan, 2000). A second interpretation of the results of both Wess et al (McMillin et al, 2011) and those we report herein is that the contributions of multiple regions of the receptor to structural organization reflects that higher order complexes beyond dimers can form.…”
Section: Discussionmentioning
confidence: 99%
“…One is that dimeric interactions may be able to occur in a number of distinct ways, including via each of the TMD V-TMD V, TMD VI-TMD VII, TMD IV-TMD V, and TMD I-TMD II interactions (McMillin et al, 2011). Observations that dimer/oligomer interactions of muscarinic receptor subtypes may be transient (Hern et al, 2010;Nenasheva et al, 2013) are certainly consistent with this concept if it predominantly reflects a "kiss and run" phenomenon (Milligan, 2000). A second interpretation of the results of both Wess et al (McMillin et al, 2011) and those we report herein is that the contributions of multiple regions of the receptor to structural organization reflects that higher order complexes beyond dimers can form.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions require that the fluorescent ligands bind with similar affinity to both protomers in the dimer (see below for discussion of ligand cooperativity within receptor dimers/oligomers; see Section II.B), and it is possible that the fluorescent ligand might stabilize the receptor in a nonrepresentative conformational state. Despite these concerns, similar studies have reached equivalent conclusions on the state of the muscarinic acetylcholine M 2 receptor in cardiac muscle (Nenasheva et al, 2013). More recently, TIR-FM was used together with SNAP-tag technology to directly label cell-surface GPCRs with organic fluorophores to dynamically monitor individual b 1 -and b 2 -adrenoceptors as well as GABA B receptors on the surface of living, transiently transfected cells (Calebiro et al, 2013).…”
Section: A the Search For The Predominant Oligomeric G Protein-couplmentioning
confidence: 99%
“…Overall, our measurements fall within a rather heterogeneous background of previous measurements of GPCR oligomerization. In particular, for the three receptors that we investigated, previous research showed either a largely monomeric [32], [29], constitutive dimeric [15] or higher order oligomeric state [29,33,34]. In one case, concentration-dependent effects were observed for both β 1 -ARs and β 2 -ARs, with a different equilibrium constant depending on the receptor [12].…”
Section: Discussionmentioning
confidence: 73%
“…The only reports supporting a higher oligomerization state for β 1 -ARs come from whole-cell BRET measurements [33] and the results may have been influenced by receptor interactions not on the plasma membrane. For M 2 Rs, single molecule imaging data [32] suggest a predominantly monomeric fingerprint, whereas fluorescence lifetime-based FRET measurements have indicated tetramers [34]. Photon counting histogram analysis indicates constitutive dimers [15].…”
Section: Discussionmentioning
confidence: 99%